Evaluation of the Effects of a Short Supplementation With Tannins on the Gut Microbiota of Healthy Subjects - Molino, Silvia; Lerma-Aguilera, Alberto; Jiménez-Hernández, Nuria; Rufián Henares, José Ángel; Francino, M. Pilar (Frontiers in Microbiology, 2022)
Western diet, high in fats and sugars and low in greens, contributes to dysbiosis of the gut microbiota, which can lead to a variety of chronic diseases related with inflammation. Supplementation with bioactive compounds can help to maintain a healthy eubiotic state. Thus, we performed a 4-weeks nutritional intervention on healthy volunteers to investigate whether a blend of natural tannin extracts could induce healthy changes in the microbial intestinal ecosystem. Changes in the composition and functionality of the microbiota could be observed from the first two weeks onwards. 16S rRNA amplicon next-generation sequencing (NGS) revealed a significant increase in microbial diversity at the end of the intervention, as well as trends towards increases in the relative abundances of several beneficial taxa, such as Ruminococcus bicirculans, Faecalibacterium prausnitzii, Lachnospiraceae UCG 010, Lachnospiraceae NK4A136, Bacteroides thetaiotaomicron and B. uniformis. Remarkably, some of the identified taxa were also identified as responsible for an increase in the production of short-chain fatty acids, microbial metabolites that contribute to the modulation of the immune system and have various other anti-inflammatory functions in the gut. Taken together, these results suggest that the tannin supplementation could exert a prebiotic effect by selectively stimulating the growth and the activity of bacteria that are advantageous for the host.